Evaluation of Aedes aegypti control intervention with pyriproxyfen by lcWGS in Manacapuru, Amazonas, Brazil - Leles, Lorena Ferreira de Oliveira; Alvarez, Marcus Vinicius Niz [UNESP]; Cortés, Jose Joaquin Carvajal; Alonso, Diego Peres [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; Luz, Sérgio Luiz Bessa (Public Library of Science (PLoS), 2024)
Background Ae. aegypti mosquitoes are considered a global threat to public health due to its ability to transmit arboviruses such as yellow fever, dengue, Zika and Chikungunya to humans. The lack of effective arboviral vaccines and etiological treatments make vector control strategies fundamental in interrupting the transmission cycle of these pathogens. This study evaluated Ae. aegypti mosquito populations pre-and post-intervention period with disseminating stations of the larvicide pyriproxyfen to understand its potential influence on the genetic structure and population diversity of these vectors. Methodology/Principal findings This study was conducted in Manacapuru city, Amazonas, Brazil, where 1,000 pyriproxyfen dissemination stations were deployed and monitored from FEB/2014 to FEB/2015 (pre-intervention) and AUG/2015 to JAN/2016 (post-intervention). Low-coverage whole genome sequencing of 36 individuals was performed, revealing significant stratification between pre-and post-intervention groups (pairwise FST estimate of 0.1126; p-value < 0.033). Tajima’s D estimates were-3.25 and-3.07 (both p-value < 0.01) for pre-and post-intervention groups, respectively. Molecular diversity estimates (Theta(S) and Theta(Pi)) also showed divergences between pre-and post-intervention groups. PCA and K-means analysis showed clustering for SNP frequency matrix and SNP geno-type matrix, respectively, being both mainly represented by the first principal component. PCA and K-means clustering also showed significant results that corroborate the impact of pyriproxy-fen intervention on genetic structure populations of Ae. aegypti mosquitoes. Conclusions/Significance The results revealed a bottleneck effect and reduced mosquito populations during intervention, followed by reintroduction from adjacent and unaffected populations by this vector. We highlighted that low-coverage whole genome sequencing can contribute to genetic and structure population data, and also generate important information to aid in genomic and epidemiological surveillance.